Tempe Drink Making Training, Physical Activity Education and Optimization of Madrasah Health Units for Madrasah Teachers in Manado - Lestari, Utami Sasmita; Angmalisang, Elvin Clara; Jayanti, Meilani (Abdimas Galuh, 2024)
Adolescence is a transition period from childhood to adulthood. Adolescence can be an indicator of health in adulthood. Consumption patterns and low physical activity in adolescents trigger obesity which is a risk factor for dyslipidemia. Tempe contains protein that affects the improvement of lipid profiles. Modifying tempe into tempe drinks makes the serving is more practical and preferred by adolescents. This activity aimed to improve the role of madrasah teachers in preventing dyslipidemia among adolescent girls through training in making tempe drinks, physical activity education and optimization of UKM. Teachers are figures who directly deal with adolescents who are students to transfer knowledge and skills in healthy living behaviors. The process of providing health education also needs to be supported by qualified facilities and infrastructure, through optimization of madrasah health units functions and programs. A total of 26 madrasah teachers participated in this activity. This activity was carried out with several stages of activities. They were counseling on dyslipidemia and the potential of tempe drinks as an effort to prevent dyslipidemia in adolescent girls and continued with training on making tempe drinks. Furthermore, counseling on physical activity and training on optimizing the function of UKM and developing health promotion media. The results of this community service activity were expected to improve the quality of adolescent health and could be implemented in the form of sustainable programs by academicians at the madrasah.